Permendikbud Implementation No. 3 Year 2020 in the Preparation of Indonesian Course Lesson Plan - Nur Aini Puspitasari; Andoyo Sastromiharjo (Universitas Indraprasta PGRI, 2021)
The purpose of this study is to describe the implementation of Permendikbud No. 3 of 2020 in the preparation of the Indonesian Language Course Learning Plan. The method used in this research is descriptive qualitative, the subject studied is the Indonesian Language Course Learning Plan from three universities in Jakarta. The data collection technique in this study is documentation by analyzing the Indonesian Language Course Learning Plan whose preparation is related to Permendikbud No. 3 of 2020. Based on the results of this study, the three universities have implemented Permendikbud No. 3 of 2020, but there are several different terms used, namely learning outcomes into subject learning outcomes, final skills which are expected to be sub-achievements of course learning, study materials into learning materials.Keywords: Permendikbud No. 3 of 2020, Course Lesson Plan, Indonesian.